2020
DOI: 10.1186/s43094-020-00128-9
|View full text |Cite
|
Sign up to set email alerts
|

Extended levobunolol release from Eudragit nanoparticle-laden contact lenses for glaucoma therapy

Abstract: Background Majorly, the reason for the permanent loss of vision is glaucoma. But the currently available common treatment methodologies such as eye drops have various disadvantages like patient incompliance due to repeated administration and poor (1–5%) bioavailability leading to poor efficiency. The objective of this research was to formulate Eudragit-based nanoparticles of levobunolol incorporated into a contact lens to obtain sustained ocular delivery of levobunolol at the therapeutics level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…The light transparency slightly decreased because of the incorporation of PSBMA nanogels. Similar results were also observed by Xu et al [ 27 ] and Maulvi et al [ 28 ] in that the transmittance of contact lenses decreased when nanoparticles were loaded. The Chinese characters (眼means: eyes) under the series of contact lenses show that optical properties were not affected ( Figure 6 b), because the incorporated nanogels were monodispersed and were nano-sized (as can be seen from SEM results), which was not likely to significantly affect visual clarity.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The light transparency slightly decreased because of the incorporation of PSBMA nanogels. Similar results were also observed by Xu et al [ 27 ] and Maulvi et al [ 28 ] in that the transmittance of contact lenses decreased when nanoparticles were loaded. The Chinese characters (眼means: eyes) under the series of contact lenses show that optical properties were not affected ( Figure 6 b), because the incorporated nanogels were monodispersed and were nano-sized (as can be seen from SEM results), which was not likely to significantly affect visual clarity.…”
Section: Resultssupporting
confidence: 90%
“…At the same time, accelerated drug release was achieved in a tear environment (pH 7.4) because of the dissolution of Eudragit S100. Kumar et al [ 28 ] also reported extended levobunolol release from pH-sensitive Eudragit nanoparticle-laden contact lenses for glaucoma therapy. However, the natural aggregation of nanoparticles reduced the optical transparency of contact lenses, and the decreased water content caused by the incorporation of nanoparticles reduced the wear comfort of the contact lenses.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al formulated Eudragit nanoparticles loaded with levobunolol by a soaking method. Loaded lenses’ physical and optical properties were not affected, and controlled long-term release was achieved for levobunolol [ 71 ]. In a rabbit tear fluid model, silicone CLs containing brimonidine-loaded nanoparticles were prepared by Xu et al A high concentration of brimonidine was achieved for 96h with nanoparticle-loaded lenses [ 72 ].…”
Section: Combination Use Of Nanotechnology and Other New Techniques F...mentioning
confidence: 99%
“…To evaluate the influence of acyl donors, namely, vinyl acetate, benzyl acetate, ethyl acetate, isobutyric anhydride, and butyric anhydride (0.1 mmol) were reacted with (RS)-12 in the presence of CAL L4777 the ee s , ee p , and C were monitored using chiral HPLC. Finally, the enzyme concentration was optimized, by conducting the reactions at optimized substrate concentration (1 mmol) by varying the selected enzyme concentration (10,20,30,40,80, and 120 mg/ml).…”
Section: Optimization For Enantioselective Esterification Of (Rs)-12mentioning
confidence: 99%
“…6 The (S)-enantiomer of β-blockers are reported to be more effective in treating diseases involving the β-adrenergic system. [7][8][9][10][11] Smith 12 and Čižm arikov a et al 13 reported that both isomers bind to the heart's β1, β2, and β3 receptors; however, the (S)-isomers have a stronger antagonistic impact because of its longer half-life with higher binding affinity for the β-receptor than the (R)-isomers. (R)-enantiomer has lower affinity for the receptor; eventually, it attaches to other receptors and can lead to undesirable consequences.…”
Section: Introductionmentioning
confidence: 99%